2019
DOI: 10.1038/s41598-019-44205-3
|View full text |Cite
|
Sign up to set email alerts
|

Dietary tryptophan deficiency and its supplementation compromises inflammatory mechanisms and disease resistance in a teleost fish

Abstract: Tryptophan participates on several physiological mechanisms of the neuroendocrine-immune network and plays a critical role in macrophages and lymphocytes function. This study intended to evaluate the modulatory effects of dietary tryptophan on the European seabass ( Dicentrarchus labrax ) immune status, inflammatory response and disease resistance to Photobacterium damselae piscicida . A tryptophan deficient diet (NTRP); a control diet (CTRL); and two other diets s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 50 publications
7
31
0
Order By: Relevance
“…The present results suggest 10 g Trp per kg diet was surplus causing health deterioration and immunosuppression in the fish. These results are in line with Machado et al () showing that surplus dietary Trp significantly compromised immune responses in fish.…”
Section: Discussionsupporting
confidence: 92%
“…The present results suggest 10 g Trp per kg diet was surplus causing health deterioration and immunosuppression in the fish. These results are in line with Machado et al () showing that surplus dietary Trp significantly compromised immune responses in fish.…”
Section: Discussionsupporting
confidence: 92%
“…First-strand cDNA was synthesized with NZY First-Strand cDNA Synthesis Kit (NZYTech). Quantitative PCR assays and primer design ( Table 1) were performed as described by Machado et al (24). The expression of the target gene was normalized using the average The efficiency of PCR reactions was calculated from serial dilutions of tissue RT reactions in the validation procedure.…”
Section: Gene Expressionmentioning
confidence: 99%
“…Studies in fish showed that increasing dietary tryptophan levels did not significantly modulate European seabass (11) and Persian sturgeon (Acipenser persicus) (23) basal innate immunerelated mechanisms activity, while a clear effect of tryptophan surplus was observed upon inflammation induction. For instance, in European seabass Azeredo et al (12) observed an inhibitory action of tryptophan on HK inflammatory transcripts while Machado et al (24) reported a compromised immune response and disease resistance to Phdp. In macrophages, tryptophan catabolism occurs through the kynurenine-niacin pathway, mediated by indoleamine 2, 3-dioxygenase (IDO) (25).…”
Section: Introductionmentioning
confidence: 99%
“…L-TRP supplementation has been investigated in other infection models. In teleost fish, L-TRP supplementation increased plasma cortisol levels, which decreased circulating leukocytes following Photobacterium infection ( 238 ). However, infected fish receiving excess dietary L-TRP displayed increased survival ( 238 ).…”
Section: L-tryptophan Metabolismmentioning
confidence: 99%
“…In teleost fish, L-TRP supplementation increased plasma cortisol levels, which decreased circulating leukocytes following Photobacterium infection ( 238 ). However, infected fish receiving excess dietary L-TRP displayed increased survival ( 238 ). In a pig model of rotavirus infection, L-TRP supplementation expanded the Foxp3 + T reg population ( 239 ).…”
Section: L-tryptophan Metabolismmentioning
confidence: 99%